2016
DOI: 10.1097/icu.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

The location of incision in cataract surgery and its impact on induced astigmatism

Abstract: The temporal incisions in cataract surgery are associated with little SIA and are appropriate choices for mild preoperative astigmatism. At higher levels of preoperative astigmatism, superior incisions are associated with better results when combined methods are not applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 59 publications
0
39
1
2
Order By: Relevance
“…The dorsonasal cornea is more susceptible to astigmatism as it is closer to the corneal center than the temporal limbus. This results in more dramatic changes in corneal topography when disrupted . Additionally, there is inherent difficulty for a right‐handed surgeon in accessing a cataract in the left eye through a dorsonasal incision, due to orbital conformation and nose anatomy, particularly in mesocephalic and dolicocephalic canines.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsonasal cornea is more susceptible to astigmatism as it is closer to the corneal center than the temporal limbus. This results in more dramatic changes in corneal topography when disrupted . Additionally, there is inherent difficulty for a right‐handed surgeon in accessing a cataract in the left eye through a dorsonasal incision, due to orbital conformation and nose anatomy, particularly in mesocephalic and dolicocephalic canines.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of the incision size and surgical induced astigmatism has been of interest to ophthalmologists, and there are reports of a positive correlation. [10][11][12] However, a recent Cochrane review has suggested that there may not be a significant, consistent impact of the size of the incision of Phacoemulsification surgery on the surgically induced astigmatism or postoperative visual acuity over a longer term. The review reported that there might be less astigmatism with coaxial micro incision Phacoemulsification surgery, but even that difference was small in the range of 0.2 D with uncertain evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with superior incisions, temporal incisions are associated with a lower level of SIA and are accordingly used for patients with low-level astig matism (16) . In our study, we used superior incisions even though our patients had a low-level astigmatism.…”
Section: Discussionmentioning
confidence: 99%